Motor Asymmetry Attenuation in Older Adults during Imagined Arm Movements - PAIZIS, CHRISTOS; Skoura, Xanthi; Personnier, Pascaline; Papaxanthis, Charalambos (Frontiers in Aging Neuroscience, 2014)
Laterality is an important feature of motor behavior. Several studies have shown that lateralization in right-handed young adults (i.e., right versus left arm superiority) emerges also during imagined actions, that is when an action is internally simulated without any motor output. Such information, however, is lacking for elderly people and it could be valuable to further comprehend the evolution of mental states of action in normal aging. Here, we evaluated the influence of age on motor laterality during mental actions. Twenty-four young (mean age: 24.7  4.4 years) and twenty-four elderly (mean age: 72.4  3.6 years) participants mentally simulated and actually executed pointing movements with either their dominant-right or nondominant-left arm in the horizontal plane. We recorded and analyzed the time of actual and mental movements and looked for differences between groups and arms. In addition, electromyographic activity from arm muscle was recorded to quantify any enhancement in muscle activation during mental actions. Our findings indicated that both groups mentally simulated arm movements without activating the muscles of the right or the left arm above the baseline level. This finding suggests that young and, notably, elderly adults are able to generate covert actions without any motor output. We found that manual asymmetries (i.e., faster movements with the right arm) were preserved in young adults for both actual and mental movements. In elderly adults, manual asymmetries were observed for actual but not for mental movements (i.e., equal movement times for both arms). These findings clearly indicate an age-related reduction of motor laterality during mental actions.